Analisis Kualitas Website Universitas Khairun Menggunakan System Usability Scale (Sus) - Muhammad, Miftah; Hizbullah, Imam; Mabud, Zulaihah (Journal of Science and Engineering, 2024)
Abstract This study analyzes the quality of the Khairun University website (unkhair.ac.id) using the System Usability Scale (SUS) method. SUS is an evaluation method consisting of 10 statements that assess effectiveness, efficiency, and user satisfaction. Data were collected by distributing questionnaires to 200 respondents who were students from 10 faculties at Khairun University. The results showed an average SUS score of 64.3, which places the quality of the website at grade "D" or based on the Acceptability range is in the "Marginal Low" range with an "OK" assessment in the adjective rating assessment. Analysis of the distribution of respondents' answers indicates that although most users find the website easy to use, there are aspects that require more attention, especially in design and navigation. Recommendations for improvement include increasing design consistency, simplifying the usage process, and adding documentation and user guides. The results of this study are expected to be a reference for improving the user experience and usability of the Khairun University website.